Synthesis of Azido Acids and Their Application in the Preparation of Complex Peptides - Moreira, Ryan; Noden, Michael; Taylor, Scott D. (Synthesis, 2020)
Azido acids are important synthons for the synthesis of complex peptides. As a protecting group, the azide moiety is atom-efficient, easy to install and can be reduced in the presence of many other protecting groups, making it ideal for the synthesis of branched and/or cyclic peptides. α-Azido acids are less bulky than urethane-protected counterparts and react more effectively in coupling reactions of difficult-to-form peptide and ester bonds. Azido acids can also be used to form azoles on complex intermediates. This review covers the synthesis of azido acids and their application to the total synthesis of complex peptide natural products.1 Introduction2 Synthesis of α-Azido Acids2.1 From α-Amino Acids or Esters2.2 Via α-Substitution2.3 Via Electrophilic Azidation2.4 Via Condensation of N-2-Azidoacetyl-4-Phenylthiazolidin- 2-Thi one Enolates with Aldehydes and Acetals2.5 Synthesis of α,β-Unsaturated α-Azido Acids and Esters3 Synthesis of β-Azido Acids3.1 Preparation of Azidoalanine and 3-Azido-2-aminobutanoic Acids3.2 General Approaches to Preparing β-Azido Acids Other Than Azi doalanine and AABA4 Azido Acids in Total Synthesis4.1 α-Azido Acids4.2 β-Azido Acids and Azido Acids Containing an Azide on the Side Chain5 Conclusions
Keywords: peptides; azido acids; azides; total synthesis; azidation; diazo transfer